BINDER DRAINAGE TEST FOR POROUS MIXTURES MADE BY VARYING THE MAXIMUM AGGREGATE SIZES - Hardiman Hardiman; M.O. Hamzah; A.A. Mohammed (Civil Engineering Dimension, 2004)
Binder drainage occurs with mixes of small aggregate surface area particularly porous asphalt. The binder drainage test, developed by the Transport Research Laboratory, UK, is commonly used to set an upper limit on the acceptable binder content for a porous mix. This paper presents the results of a laboratory investigation to determine the effects of different binder types on the binder drainage characteristics of porous mix made of various maximum aggregate sizes 20, 14 and 10 mm. Two types of binder were used, conventional 60/70 pen bitumen, and styrene butadiene styrene (SBS) modified bitumen. The amount of binder lost through drainage after three hours at the maximum mixing temperature were measured in duplicate for mixes of different maximum sizes and binder contents. The maximum mixing temperature adopted depends on the types of binder used. The retained binder is plotted against the initial mixed binder content, together with the line of equality where the retained binder equals the mixed binder content. The results indicate the significant contribution of using SBS modified bitumen to increase the target bitumen binder content. Their significance is discussed in terms of target binder content, the critical binder content, the maximum mixed binder content and the maximum retained binder content values obtained from the binder drainage test. It was concluded that increasing maximum aggregate sizes decrease the maximum retained binder content, critical binder content, target binder content, maximum mixed binder content, and mixed content for both binders, but however for all mixtures, SBS is the highest.